1976
DOI: 10.1093/oxfordjournals.jbchem.a131193
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Crystallization, and Some Properties of Creatine Amidinohydrolase from Pseudomonus putida

Abstract: A method was developed for purification and crystallization of creatinase [creatine amidinohydrolase, EC 3.5.3.3] from Pseudomonas putida var. naraensis C-83. The purified preparation appeared homogeneous on disc electrophoresis and ultracentrifugation and had a molecular weight of 94,000. It was most active at pH 8 and stable between pH 6 and 8 for 24 hr at 37 degrees. SDS-polyacrylamide gel electrophoresis indicated that the native enzyme was made up of two subunit monomers, the molecular weights of which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Related to this metabolic flexibility, close to 10% of P. aeruginosa genes are predicted to encode transcription factors (39), many of which likely allow the organism to sense potential nutrient sources and regulate enzymatic pathways to exploit a variety of metabolic niches. Sarcosine is present in a range of environments inhabited by P. aeruginosa, although it is likely encountered most often as an intermediate metabolite of glycine betaine, carnitine, glyphosate, or creatine catabolism (6)(7)(8)(9)(10)(11)(12)(13)(14)22) (Fig. 1A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to this metabolic flexibility, close to 10% of P. aeruginosa genes are predicted to encode transcription factors (39), many of which likely allow the organism to sense potential nutrient sources and regulate enzymatic pathways to exploit a variety of metabolic niches. Sarcosine is present in a range of environments inhabited by P. aeruginosa, although it is likely encountered most often as an intermediate metabolite of glycine betaine, carnitine, glyphosate, or creatine catabolism (6)(7)(8)(9)(10)(11)(12)(13)(14)22) (Fig. 1A).…”
Section: Discussionmentioning
confidence: 99%
“…Burns and deep lacerations also expose P. aeruginosa to readily available sarcosine precursors, including carnitine in muscle tissue and choline released from damaged cell membranes (7,8). Furthermore, Pseudomonas putida and some isolates of P. aeruginosa can metabolize creatine to generate sarcosine (9)(10)(11), while other pseudomonads obtain sarcosine through metabolism of the herbicide glyphosate (12)(13)(14).…”
mentioning
confidence: 99%
“…Specific enzyme activity of creatinase was determined according to the method set up by Yoshimoto et al [3] 0.1 ml enzyme solution was added into a 0.9 ml 50 mM potassium phosphate buffer (PBS, pH7.0) containing 100 mM creatine as substrate. After 10 min incubation at 37 8C, 2.0 ml p-dimethylaminobenzaldehyde solution (2.0 g p-dimethylaminobenzaldehyde dissolved in 100 ml dimethylsulfoxide, then 15 ml HCl stock added) was added to stop the reaction by incubation at 25 8C for 20 min and absorbance was measured against the blank at 435 nm.…”
Section: Creatinase Activity Assaymentioning
confidence: 99%
“…Coll et al [20] and Yoshimoto et al [21] have shown that the modification of sulfhydryl groups on creatine amidinohydrolase causes complete loss of activity. This is interesting since the Cys residues are distant from the active site and have no known role in catalysis [20,22].…”
Section: Effect Of Silver On Enzyme Activitymentioning
confidence: 99%